Telefonoaudiologia: Ciência e tecnologia em saúde - Spinardi, Ana Carulina Pereira; Blasca, Wanderléia Quinhoneiro; Wen, Chao Lung; Maximino, Luciana Paula [UNESP] (FapUNIFESP (SciELO), 2009)
Background: distance learning (DL) is becoming a higher education modality with a meaningful impact. It offers students flexibility, mobility and choices. Also it can reach a greater number of professionals and students in a more effective way, when compared to other learning modalities, without losing quality. Brazil needs to develop direct actions to DL in the fields of Speech-Language Pathology and Hearing, due to its great continental territory (8,514,215.3Km 2) and irregular distribution of professionals who work in these specific fields (i.e. this situation emphasizes the differences in quality and availability of services offered throughout the country). Heterogeneity in the quality and availability of services is also aggravated by the absence of a national strategy for continued education in order to recycle health professionals. This situation causes important differences in the knowledge and abilities of specialists from one region to the next. Aim: to present Telehealth studies in the field of Speech-Language Pathology and Hearing that were developed in the last five years. Conclusion: the analyzed data indicate that more studies are needed in this specific field. These studies should aim at improving the quality and access to services which in turn would improve prevention, diagnosis and treatment of communication disorders.
Telehealth in speech-language pathology and hearing: Science and technology
Keywords: Distance education; Speech-language pathology; Telehealth; Telemedicine; Brazil; education; human; review; speech disorder; standard; telemedicine; Education, Distance; Humans; Speech-Language Pathology; Brazil (09450); Communication Disorders (13625); Distance Learning (19530); Health Care Practitioners (31130); Hearing (31150); Language Pathology (43250); Language Therapists (83215); Speech; Speech Pathology (82650)